2021
DOI: 10.1029/2020rs007119
|View full text |Cite
|
Sign up to set email alerts
|

Signal‐In‐Space Performance Under Multiconstellation Environment From an Indian Low Latitude Station

Abstract: Global Navigation Satellite System (GNSS) signals have become a useful tool to analyze signal‐in‐space performance in the presence of ionospheric perturbations with a view to improve the performance of satellite‐based systems and services. For this purpose, continuous monitoring of the signal tracking capabilities of commercial GNSS receivers is a priority, particularly from regions around the crests of Equatorial Ionization Anomaly (EIA), which experiences some of the worst‐case scenarios attributed to ionosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Scintillation effects on L1 and L2 signals of GLONASS along with a comparative study of simultaneous scintillation occurrence at GPS and GLONASS have been reported earlier using observations from four different stations within Brazilian sector (de Oliveira Moraes et al., 2018). A multi‐frequency comparison of signal fading at GPS, GLONASS and Galileo, during period of scintillation has also been reported previously from a low‐latitude station (Biswas & Paul, 2021).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Scintillation effects on L1 and L2 signals of GLONASS along with a comparative study of simultaneous scintillation occurrence at GPS and GLONASS have been reported earlier using observations from four different stations within Brazilian sector (de Oliveira Moraes et al., 2018). A multi‐frequency comparison of signal fading at GPS, GLONASS and Galileo, during period of scintillation has also been reported previously from a low‐latitude station (Biswas & Paul, 2021).…”
Section: Introductionsupporting
confidence: 64%
“…Equatorial and low‐latitude region of the Earth's ionosphere being most dynamic out of all, in terms of formation and evolution of ionization density depletions, transionospheric satellite links used for communication and navigation are most vulnerable to the effects of scintillation in these locations (Bandyopadhayay et al., 1997; DasGupta et al., 2004), even to the extent of complete signal outage (Biswas & Paul, 2021; de Oliveira Moraes et al., 2017; Guo et al., 2019). This paper focuses on the dynamics of satellite motion as observed from a low latitude station, in order to interpret its effect on tracking loop performance of receivers, in presence of ionospheric scintillation, caused by irregularity structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scintillation caused by diffraction can occur when the radio wave interacts with a medium with many small changes in refractive index, whereas refractive scintillation takes place when the wave falls upon increased or decreased phase velocity medium (Kintner et al., 2007). Effects of ionospheric scintillation on satellite signal can be intense and most severe in the low‐latitude and equatorial regions, as some of the worst instances of signal perturbation can be observed here, even to the extent of complete loss‐of‐lock of signal (Biswas et al., 2019; Biswas & Paul, 2021; Roy & Paul, 2013).…”
Section: Introductionmentioning
confidence: 85%
“…A similar study but with data from only one equinoctial month of solar active year 2014 was performed by Biswas and Paul [41] in terms of occurrence and duration of cycle slip and LoL at the northern anomaly crest location in India. They highlight the susceptibility of GLONASS L1 CA among all GNSS signals and the resistant characteristics of Galileo signals among the primary L1 signals from only three constellations (GPS, GLONASS, Galileo).…”
Section: Introductionmentioning
confidence: 87%